Vapor-Liquid Interfaces, Bubbles and Droplets Fundamentals and Applications - Fujikawa, Shigeo; Yano, Takeru; Watanabe, Masao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Physically correct boundary conditions on vapor-liquid interfaces are essential in order to make an analysis of flows of a liquid including bubbles or of a gas including droplets. Suitable boundary conditions do not exist at the present time. This book is concerned with the kinetic boundary condition for both the plane and curved vapor-liquid interfaces, and the fluid dynamics boundary condition for Navier-Stokes(fluid dynamics) equations. The kinetic boundary condition is formulated on the basis of molecular dynamics simulations and the fluid dynamics boundary condition is derived by a perturbation analysis of Gaussian-BGK Boltzmann equation applicable to polyatomic gases. The fluid dynamics boundary condition is applied to actual flow problems of bubbles in a liquid and droplets in a gas.
Historical Review on Vapor-Liquid Interfaces -- Molecular Dynamics of Vapor-Liquid Interfaces with Evaporation and Condensation -- Boundary Conditions for Fluid-Dynamics-Type Set of Equations Based on Molecular Gas Dynamics -- Measurement of Evaporation and Condensation Coefficients by Shock Wave and Sound Resonance Methods -- Applications to Bubbles and Droplets -- Appendices.
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Fluid- and Aerodynamics